Isokinetic assessment of shoulder complex strength in adolescent elite synchronized swimmers - Aguado-Henche, S.; Slocker de Arce, A.; Carrascosa-Sánchez, J.; Bosch-Martin, A.; Cristóbal-Aguado, S. (Journal of Bodywork and Movement Therapies, 2018)
Children and adolescent participation in sport has increased in recent years. Synchronized swimming requires correct muscle balance in the shoulder complex. The purpose of this study was to establish isokinetic strength profiles and peak torque ratios of shoulder internal and external rotator muscles in a female high-level synchronized swimming team. Twenty-six adolescent female high-level synchronized swimmers, aged 12-14, participated in this study. Maximal bilateral shoulder concentric external and internal rotation force was measured at 60°/s (5 repetitions) and 180°/s (15 repetitions). The isokinetic concentric strength generated by the internal rotator muscles was significantly higher (p < 0.05) than by the external rotators in both limbs and at both velocities. Significant bilateral differences in the external rotation (ER):internal rotation (IR) strength ratio were noted at 60°/s. Isokinetic assessment is essential in sports medicine, since it is the only test capable of diagnosing any shoulder strength deficit.